Reading-Related Activities in English Textbook and How the Texts are Exploited in Junior High Schools - Ni Kadek Yuli Cahyani; Artini, Luh Putu; Wahyuni, Luh Gede Eka (Journal of Education Reseach and Evaluation, 2023)
In order to make the teaching and learning reading process run effectively, it is important to consider the suitability of reading activities which contain in English textbook. This study aims to analyze reading-related activities that are available in English textbook for Grade 9 and observe how the reading texts are exploited in English classes by the English teacher. This study employed qualitative descriptive method in which the data collection was done through document analysis, classroom observation, and interview. The data were analyzed by the criteria of reading-related activities. The result showed that, there are several reading-related activities discovered from the English textbook of grade 9. Then, reading-related activities that occurred most frequently in the textbook are skimming/scanning-details (short answer) and questioning-short answer. Meanwhile, the English teacher use text exploitation strategies. According to the interview, the English teacher mostly relied on the existing reading activities in the English textbook. Thus, the use of English textbook in teaching and learning, especially the use of reading activities it is very essential in developing students' reading skill.